A 35-year-old woman with influenza A-associated thrombotic thrombocytopenic purpura. Issue 4 (June 2015) - Jonsson, Maria K.; Hammenfors, Daniel; Oppegaard, Oddvar; Bruserud, Øystein; Kittang, Astrid Olsnes
<x xml:space="preserve">Abstract</x> A previously healthy 35-year-old woman presented with severe thrombotic thrombocytopenic purpura (TTP) affecting several organs and concomitant influenza A infection. On admission to hospital, haemoglobin was 5.4 g/dl, platelet count 6 × 109/l, Schistocyte count in peripheral blood 5%, and throat swab positive for influenza A RNA. The patient was treated with antiviral medication and transfusions of fresh frozen plasma before plasma exchange therapy with excellent response. Plasmaphereses were attenuated after 5 days, resulting in TTP relapse 3 days later. A disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13) protein was very low (<0.04 U/l) and anti-ADAMTS13 elevated (>2 U/l), consistent with acquired TTP. Platelet counts normalized after five additional plasma exchanges and oral corticosteroids. Antinuclear antibodies and subgroup anti-Ro/Sjögren's syndrome A antigen (SSA) were detected in serum and have remained borderline-elevated, although evaluation during TTP, recovery and follow-up have lacked clinical manifestations of connective tissue disease. Influenza A infection induced production of ADAMTS13 inhibitor, which resulted in TTP in a patient with circulating antinuclear antibodies, lacking other manifestations of connective tissue disease.